Multiplexed Detection of O-GlcNAcome, Phosphoproteome, and Whole Proteome within the Same Gel - Cieniewski-Bernard, Caroline; Dupont, Erwan; Deracinois, Barbara; Lambert, Matthias; Bastide, Bruno (Frontiers in Endocrinology, 2014)
The cellular diversity of proteins results in part from their post-translational modifications. Among all of them, the O-GlcNAcylation is an atypical glycosylation, more similar to phosphorylation than classical glycosylations. Highly dynamic, reversible, and exclusively localized on cytosolic, nuclear and mitochondrial proteins, O-GlcNAcylation is known to regulate almost all if not all cellular processes. Fundamental for the cell life, O-GlcNAcylation abnormalities are involved in the etiology of several inherited diseases. Assessing to O-GlcNAcylation pattern will permit to get relevant data about the role of O-GlcNAcylation in cell physiology. To get understanding about the role of O-GlcNAcylation, as also considering its interplay with phosphorylation, the O-GlcNAc profiling remains a real challenge for the community of proteomists/glycoproteomists. Due to development of multiplexed proteomics based on fluorescent detection of proteins, there is growing body of evidence about the proteome knowledge’s. We propose herein a multiplexed proteomic strategy to detect O-GlcNAcylated proteins, phosphoproteins, and the whole proteome within the same bidimensional gel. In particular, we investigated the phosphoproteome through the ProQ Diamond staining, while the whole proteome was visualized through Sypro Ruby staining, or after the labeling of proteins with a T-Dye fluorophore. The O-GlcNAcome was revealed by the way of the Click chemistry and the azide-alkyne cycloaddition of a fluorophore on GlcNAc moieties. This method permits, after sequential image acquisition, the direct in-gel detection of O-GlcNAcome, phosphoproteome and whole proteome.